2015
DOI: 10.1515/ip-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

The use of computer-delivered structured tasks in pragmatic instruction: An exploratory study

Abstract: This study examines the effect of oral practice via computer-delivered structured tasks (CASTs) with native speaker (NS) models and open-ended tasks without NS input (i.e., learner-leaner role-plays) on pragmatic development of second language learners. While prior studies have indicated that structured tasks afford more opportunities for focus on form (FonF) than open-ended tasks (Lee and VanPatten 2003;Lyster 2004;Ranta and Lyster 2007;Skehan and Foster 1999; Tavakoli and Foster 2011), differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(11 citation statements)
references
References 45 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Studies examining structured practice of pragmatic routines found that learners could focus on both linguistic form and the content of their responses (Sydorenko, 2015;Sydorenko & Tuason, 2016). We thus categorized changes made into two categories: form or content.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies examining structured practice of pragmatic routines found that learners could focus on both linguistic form and the content of their responses (Sydorenko, 2015;Sydorenko & Tuason, 2016). We thus categorized changes made into two categories: form or content.…”
Section: Discussionmentioning
confidence: 99%
“…First, responses to an interlocutor in a particular situation can be practiced an unlimited number of times: oral rehearsal alone, without any feedback, can lead to improvements in fluency, accuracy, and complexity (see Ellis, 2009). Second, as previous research indicates (Sydorenko, 2015;Sydorenko & Tuason, 2016), language learners can incorporate model input from expert speakers into their production, and do so simultaneously during their interaction with expert speakers. Thus, it was envisioned that similar input incorporation may take place as learners use SimCon.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study, comparing an oral role playing activity (between a learner and a native speaker) with an application letting the students answer orally after a video prompt, also provides an interesting insight: the dialogue-based CALL users were paying stronger attention to form, even with spoken interactions (Sydorenko, 2015). The researcher observed more signs of uptake in the computer program, as learners were incorporating sequences and strategies from the input into their speech, and accuracy was improving across iterations.…”
Section: Observational Studiesmentioning
confidence: 99%